On developing Block‐Chain based Secure Storage Model (BSSM) with auditing and integrity analysis in the cloud - Apirajitha, Pichai Subramanian; Sathianesan, Godfrey Winster (Concurrency and computation, 2024)
Summary In present scenario, Cloud Computing is developing vast, as the resources are utilized by many people and provided on‐demand. Recent works on cloud reports the success rates of cyber activities using cloud models for deceptive actions, because of its significant features and lack of apposite forensic models for cloud. For developing a cloud model for forensic support is an important and intricate issue like, directorial and technical challenges due to system distribution, virtualization, and dynamic characteristic of nodes. Considering the issues, this article develops a Block‐chain based Secure Storage Model (BSSM) incorporating Integrity and Auditing Examination Model for evaluating reliability of forensic data and auditing for validation. Moreover, this model effectively works on the domain of Forensic as a Service (FaaS) in cloud. The forensic data are formed into block‐chain for ensuring security. The model also aids in reducing the storage space effectively and the auditing and integrity analysis model incorporated in this work minimizes the dependency of trusts on Cloud Service Provider (CSP). And, the evaluation results show that the proposed model effectively achieves the objective in better way than compared works.